Diversidad y composición florística del banco de semillas del suelo en ecosistemas con diferente estado de conservación - Villa Jaramillo, María Gabriela (2025)
Given the continuous degradation of forest remnants as a result of anthropic activities such as deforestation, expansion of the agricultural frontier, demographic increase, among others, areas have been identified for the restoration of ecosystems through natural regeneration processes, however, one of the main problems that arises in its implementation is the scarce knowledge of key ecological processes to facilitate restoration such as the soil seed bank, a process that would facilitate the permanence of certain plant species considered ecologically important for Andean ecosystems. The objective of the study was to contribute with information on the ecology of the soil seed bank in ecosystems with different conservation status in the Southern Region of Ecuador. Two ecosystems were selected: reference and disturbed in the rural parishes of San Lucas and Santiago. Soil samples were obtained from temporary plots of 1 × 1 m nested systematically in plots of 20 × 20 m. 25 samples were sampled from both the reference and disturbed ecosystems. Twenty-five samples of both the organic and mineral layers were sampled at 10 cm depth. The monitoring of the soil seed bank was carried out for a period of four months, where floristic composition, structural parameters, survival and similarity between ecosystems were evaluated. The disturbed ecosystem presented a higher number of germinated individuals, with the presence of herbaceous and shrub species of the families Cyperaceae, Lamiaceae, Solanaceae and Asteraceae, with a survival rate of 74.02 %. The species with the highest number of individuals was Cyperus sp. whereas, the reference ecosystem presented a lower number of germinated individuals with herbaceous and shrub species of the families Asteraceae, Phytolaccaceae and Violaceae and a survival of 67.95 %, the species with the highest number of individuals was Indeterminate 1. The similarity of plant species in the disturbed ecosystem between organic and inorganic layers was 92.3 %, sharing 12 species; while, the organic layer and the mineral layer in the reference ecosystem presented a similarity index of 75 %, sharing six species. In relation to the vegetation cover, the disturbed ecosystem had a similarity of 13.00 %, sharing three individuals, while the reference ecosystem did not present similarity. The soil seed bank of ecosystems with different conservation status is important for the processes of natural regeneration and ecological succession, since they contribute to the permanence of local species, which would facilitate the future establishment of patches with native plant species of interest to society.